Thermal kinetics of biochar-ethylene vinyl acetate for waste-to-energy: Particle swarm optimization, cloud computing, and artificial intelligence - Wei-Hsin Chen; Che-An Lin; Partha Pratim Biswas; Chih-Chun Chen; Biqing Liang; Sheng-Lun Lin; Hwai Chyuan Ong; Aristotle T. Ubando (Fuel, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A horizon scan of global issues on forests and livelihoods for 2026 - Matilda Kabutey-Ongor; Katie Devenish; Mariana Hernández-Montilla; Lucas Alencar; Sandra Barragan-Contreras; Victorine Che Thöner; Reem Hajjar; Yayan Hidayat; David Kaimowitz; Birendra K. Karna; Duong T. Khuu; Anders C. Krogh; et al. (Forest Policy and Economics, 2026)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Shell-based agricultural wastes biomass valorization for biofuel production: a bibliometric analysis into the circular bioeconomy - Abdulrahman Oyekanmi Adeleke; Kazeem Alasinrin Babatunde; Saraswathy Kasavan; Rohayu Che Omar; Temitope T. Dele-Afolabi (Environmental Science and Pollution Research, 2024)

Estimating concentrations for particle and gases in a mechanically ventilated building in Hong Kong: multivariate method and machine learning - Wenwei Che; Alison T. Y. Li; Alexis K. H. Lau (Air Quality, Atmosphere & Health, 2022)

Hunting for cultivable Micromonospora strains in soils of the Atacama Desert - Lorena Carro; Valeria Razmilic; Imen Nouioui; Lee Richardson; Che Pan; Patrycja Golinska; Juan A. Asenjo; Alan T. Bull; Hans-Peter Klenk; Michael Goodfellow (Antonie van Leeuwenhoek, 2018)

Extreme snow hazard and ground snow load for China - H. M. Mo; L. Y. Dai; F. Fan; T. Che; H. P. Hong (Natural Hazards, 2016)

Complex longitudinal diversification across South China and Vietnam in Stejneger's pit viper, Viridovipera stejnegeri (Schmidt, 1925) (Reptilia: Serpentes: Viperidae) - Peng Guo; Qin Liu; Fei Zhu; Guang H. Zhong; Xin Chen; Edward A. Myers; Jing Che; Liang Zhang; Thomas Ziegler; Truong Q. Nguyen; Frank T. Burbrink (Molecular Ecology, 2016)
Viridovipera stejnegeri is one of the most common pit vipers in Asia, with a wide distribution in southern China and Vietnam. We investigated historical demography and explored how the environment and climatic factors have shaped genetic diversity and the evolutionary history of this venomous snake. A total of 171 samples from 47 localities were sequenced and analysed for two mitochondrial gene fragments and three nuclear genes. Gene trees reveal the existence of two well‐supported clades (Southwest China and Southeast China) with seven distinct and strongly supported, geographically structured subclades within V. stejnegeri . Estimation of divergence time and ancestral area suggests that V. stejnegeri originated at ~6.0 Ma in the late Miocene on the Yunnan–Guizhou Plateau. The estimated date of origin and divergence of the island populations of Taiwan and Hainan closely matches the geological origin of the both islands. The mt DNA gene tree reveals the presence of west–east diversification in V. stejnegeri populations. Complex orogenesis and heterogeneous habitats, as well as climate‐mediated habitat differentiation including glacial cycles, all have influenced population structure and the distribution of this taxon. The validity of V. stejnegeri chenbihuii is questionable, and this subspecies most probably represents an invalid taxon.

Induction of Experimental Autoimmune Encephalomyelitis With Recombinant Human Myelin Oligodendrocyte Glycoprotein in Incomplete Freund’s Adjuvant in Three Non-human Primate Species - Krista G. Haanstra; S. Anwar Jagessar; Anne-Laure Bauchet; Mireille Doussau; Claire-Maëlle Fovet; Nicole Heijmans; Sam O. Hofman; Jennifer van Lubeek-Veth; Jeffrey J. Bajramovic; Yolanda S. Kap; Jon D. Laman; Hélène Touin; et al. (Journal of Neuroimmune Pharmacology, 2013)

Development of monoclonal antibody-based galactomannoprotein antigen-capture ELISAs to detect Aspergillus fumigatus infection in the invasive aspergillosis rabbit models - Z.-Y. Wang; J.-P. Cai; L.-W. Qiu; W. Hao; Y.-X. Pan; E. T. K. Tung; C. C. Y. Lau; P. C. Y. Woo; S. K. P. Lau; K.-Y. Yuen; X.-Y. Che (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Role of nitrogen fixation in the autecology of Polaromonas naphthalenivorans in contaminated sediments - Buck T. Hanson; Jane M. Yagi; Che Ok Jeon; Eugene M. Madsen (Environmental Microbiology, 2012)
Summary Polaromonas naphthalenivorans strain CJ2 is a Gram‐negative betaproteobacterium that was identified, using stable isotope probing in 2003, as a dominant in situ degrader of naphthalene in coal tar‐contaminated sediments. The sequenced genome of strain CJ2 revealed several genes conferring nitrogen fixation within a 65.6 kb region of strain CJ2's chromosome that is absent in the genome of its closest sequenced relative Polaromonas sp. strain JS666. Laboratory growth and nitrogenase assays verified that these genes are functional, providing an alternative source of nitrogen in N‐free media when using naphthalene or pyruvate as carbon sources. Knowing this, we investigated if nitrogen‐fixation activity could be detected in microcosms containing sediments from the field site where strain CJ2 was isolated. Inducing nitrogen limitation with the addition of glucose or naphthalene stimulated nitrogenase activity in amended sediments, as detected using the acetylene reduction assay. With the use of fluorescence microscopy, we screened the microcosm sediments for the presence of active strain CJ2 cells using a dual‐labelling approach. When we examined the carbon‐amended microcosm sediments stained with both a strain CJ2‐specific fluorescent in situ hybridization probe and a polyclonal fluorescently tagged antibody, we were able to detect dual‐labelled active cells. In contrast, in sediments that received no carbon addition (showing no nitrogenase activity), no dual‐labelled cells were detected. Furthermore, the naphthalene amendment enhanced the proportion of active strain CJ2 cells in the sediment relative to a glucose amendment. Field experiments performed in sediments where strain CJ2 was isolated showed nitrogenase activity in response to dosing with naphthalene. Dual‐label fluorescence staining of these sediments showed a fivefold increase in active strain CJ2 in the sediments dosed with naphthalene over those dosed with deionized water. These experiments show that nitrogen fixation may play an important role in naphthalene biodegradation by strain CJ2 and contribute to its ecological success.

Atmospheric Aerosols over a Southwestern Region of Texas - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; Rafael Tadmor; T. C. Ho (Environmental Modeling & Assessment, 2009)

Atmospheric Aerosol over a Southeastern Region of Texas: Chemical Composition and Possible Sources - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; T. C. Ho (Environmental Modeling & Assessment, 2009)

Typing keystroke duration changed after submaximal isometric finger exercises - Che-Hsu (Joe) Chang; Peter W. Johnson; Jeffrey N. Katz; Ellen A. Eisen; Jack T. Dennerlein (European Journal of Applied Physiology, 2009)

Mana-Hox displays anticancer activity against prostate cancer cells through tubulin depolymerization and DNA damage stress - Che-Jen Hsiao; Yunn-Fang Ho; John T.-A. Hsu; Wei-Ling Chang; Yi-Cheng Chen; Ya-Ching Shen; Ping-Chiang Lyu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Insights into oxygen-cation bonding in fresnoite-type structures from O K- and Ti L23-electron energy-loss spectra and ab initio calculations of the electronic structure - P. A. van Aken; T. Hche; F. Heyroth; R. Keding; R. Uecker (Physics and Chemistry of Minerals, 2004)